Landscape character: a knowledge mapping analysis using CiteSpace - Zhuang, Q. D.; Hussein, M. K.; Ariffin, N. F. M.; Yunos, M. Y. M. (Springer Nature, 2022)
The purpose of this study is to determine the overall structure and relative comprehensive understanding of the development status of landscape character research visually. A knowledge mapping analysis of 308 academic papers in Web of Science published between 1967 and 2021 related to landscape character using CiteSpace from multiple perspectives including collaboration network, co-citation, and co-occurrence was conducted in this study. The results suggest that the quantity of publications about landscape character has increased rapidly and its staged characteristics have been exposed. The distribution of disciplines, countries, and research organizations, as well as the productive authors involved in landscape character research were identified. The research revealed the high-frequency themes sorted out in current literature including classification, biodiversity, perception, GIS, management, conservation, etc. Finally, the study visualized emerging research frontiers and deeply depicted six of them which consist of the cultural landscape, nonexpert-based landscape aesthetics evaluation, understanding public interest, landscape metrics, practical application, and using public participation GIS. This study provided a comprehensive prospect for the further study of landscape character and filled the gap in this field. It demonstrated that through the approach of CiteSpace can draw a sketch structure and potential relationship of landscape character researches. All these provide readers especially potential researchers with an overall and in-depth understanding of landscape character, indicating the research development and characteristics in this field.